One Million Voices Global Review: A review and analysis of existing citizen science initiatives and projects supporting agroecology and agroecological transitions - van Dien, L.C.; Fuchs, L.E. (CIFOR-ICRAF, 2023)
This report summarizes the results of a global review and analysis of citizen science projects supporting agroecology and agroecological transitions. The purpose of the review is to provide information on existing projects and inspire the development of a citizen science tool that enables inclusive participation in agroecology movements. The report aims to promote sustainable adoption of agroecology, fill knowledge gaps, and avoid duplication. It also contributes to four regional dialogues that were held to support the development of the One Million Voices of Agroecology digital platform.